DNA As The Determination of Descendant of Children Outside of Marriage Under The Perspective of Ibn Taimiyyah - Fageh, Achmad (Al-Hukama': The Indonesian Journal of Islamic Family Law, 2021)
The focus of this study was ibn Taimiyyah's ijtihad on the status of children outside marriage and its correlation with the determination of DNA as normative evidence of child status. The purpose of the research was to find out the results of Ibn Taimiyyah's ijtihad related to the position of children outside marriage and its correlation to the determination of DNA as a valid child status. This type of research is in the form of a literature study ijtihad Ibn Taimiyyah in Majmu' Fatawa's book using descriptive deductive analysis. The determination of child' in Islamic perspective has  significant meaning, with resolution can be known relationship between child and father. His Father's decision is the first right of a child when it is born into the world that must be fulfilled. According to Ibn Taimiyyah, adulterous children can still be recognized by unfaithful men and have mahram relationships with both parents. Adulterous children have mahram relationships with the man, provided that the man realizes the adulterous child as his son. Then according to Ibn Taimiyyah's view, civil relations, both inheritance, living, and guardianship of unfaithful children with adulterous men who admit the child is severed due to adultery, Ibn Taymiyyah's opinion has a solid correlation with the verdict of Mk No. 46/PUU-VIII/2010,  namely the affirmation of his father of an unmarried child having a blood relationship and civil relations with his biological father and father's family as evidenced by DNA tests. The legal relationship of an out-of-wedlock child with his biological father gives rise to the right and obligation in return. [Fokus penelitian ini adalah ijtihad ibnu Taimiyyah tentang status anak di luar perkawinan dan korelasinya dengan penetapan DNA sebagai bukti normatif status anak. Tujuan penelitian ini untuk mengetahui hasil ijtihad Ibn Taimiyyah terkait posisi anak di luar perkawinan dan korelasinya dengan penetapan DNA sebagai status anak yang sah. Penelitian ini berupa studi literatur ijtihad Ibn Taimiyyah dalam buku Majmu' Fatāwā dengan menggunakan analisis deduktif deskriptif. Penentuan anak dalam perspektif Islam memiliki arti yang signifikan, dengan tekad dapat diketahui hubungan antara anak dan ayah. Selain itu, keputusan Ayahnya adalah hak pertama seorang anak ketika lahir ke dunia yang harus dipenuhi. Menurut Ibn Taimiyyah, anakanak hasil perbuatan zina masih bisa dikenali dan memiliki hubungan mahram dengan kedua orang tuanya. Anak-anak hasil zina memiliki hubungan mahram dengan ayahnya, asalkan ayahnya menyadari anak tersebut sebagai anaknya. Selanjutnya pandangan Ibn Taimiyyah, terkait hubungan sipil, baik warisan, hidup, maupun perwalian anak-anak hasil zina seorang lelaki yang mengakui anaknya terputus akibat perzinaan. Pendapat Ibn Taymiyyah ini memiliki korelasi yang kuat dengan putusan MK Nomor 46/PUU-VIII/2010, yaitu penegasan nasab anak di luar nikah memiliki hubungan darah dan hubungan keperdataan dengan ayah biologis dan keluarga ayahnya. hubungan hukum anak di luar nikah dengan ayah biologisnya itu memunculkan hak dan kewajiban secara timbal balik.]